The perception of public sector auditors on performance audit in Malaysia - Loke, Chew Har; Ismail, Suhaiza; Abdul Hamid, Fatima (Emerald Group Publishing Limited, 2016)
Purpose – The objective of the study is to explore the perception of public sector auditors on performance audit in Malaysian public sector entities. In particular, this study elicits the respondents’ opinion on whether the effectiveness element should be part of the elements of performance audit, the need for involvement of auditors in policy making, relevant experts to undertake a performance audit, major constraints in carrying out performance audit and the possibility of performance audit to improve public administration. Design/methodology/approach – The study employed postal questionnaire method to seek the perception of the auditors. The questionnaire was distributed to the population of public sector auditors in the National Audit Department in Malaysia and a total of 503 usable responses were received. The responses were analysed using descriptive statistical analysis including mean score and mean score ranking. Findings - The results reveal that auditors were of the opinion that effectiveness element should be part of the performance audit and the public sector auditors should be given the opportunity to influence policy decisions. In addition, the results show that public auditor is not the only profession to carry out performance audit, but to team up with other groups of profession. In relation to constraints in performance audit, ‘Lack of cooperation and commitment from auditees in conducting a performance audit’ was claimed to be the most top constraint. Furthermore, performance audit was claimed to be able to enhance public accountability, as well as to be more economical, efficiency and effectiveness in utilising public resources. Originality/value – This paper is one of the few studies on public sector auditing particularly on performance auditing in the context of a developing country (i.e Malaysia).